Varietas Delectat: Exploring Natural Variations in Nitrogen-Fixing Symbiosis Research - Wang, Ting; Balla, Benedikta; Kovács, Szilárd; Kereszt, Attila (Frontiers in Plant Science, 2022)
Nitrogen fixing symbiosis between leguminous plants and soil bacteria collectively called rhizobia plays an important role in the global nitrogen cycle and is an essential component of sustainable agriculture. Genetic determinants directing the development and functioning of the interaction have been identified with the help of a very limited number of model plants and bacterial strains. Most of the information obtained from the study of model systems could be validated on crop plants and their partners. Investigation of soybean cultivars and different rhizobia, however, has revealed the existence of ineffective interactions between otherwise effective partners that resemble gene-for-gene interactions described for pathogenic systems. Since then, incompatible interactions between natural isolates called ecotypes of model plants and different bacterial partner strains have been reported. Moreover, diverse phenotypes of both bacterial mutants on different host plants and plant mutants with different bacterial strains have been described. Identification of the genetic factors behind the phenotypic differences did already and will reveal novel functions of known genes/proteins, the role of certain proteins in some interactions and the fine regulation of the steps during nodule development.